Science and technology teachers’ opinions about problems faced while teaching 8th grade science unit “force and motion” and suggestions for solutions - Bozdoğan, Aykut Emre; Uzoğlu, Mustafa (Journal of Turkish Science Education, 2015)
The aim of this study is to explore the problems encountered while teaching force and motion unit in 8th grade science and technology course from teachers’ perspectives and offer solutions to eliminate these problems. The study was conducted with 248 science and technology teachers working in 7 regions in Turkey in 2012-2013 academic year. Descriptive method was used in the research. The data of the research was obtained with a questionnaire developed by the researchers. Content analysis, arithmetic mean, and standard deviation were used for the analysis of the data. The teachers stated that the problems and solutions in force and motion unit in science and technology course depending on time, text book and work book, lack of connection to daily life, feature of the unit, students and implementations were examined. As a result of the study the teachers justified that abstract and complicated subject, lack of equipment and tools, and students’ not being able to use scientific process skills adequately were the problems in force and motion unit in science and technology course. To solve the problems, the teachers suggested that course hours should be increased, labs should be improved, more equipment and tools should be provided and teachers should give more opportunities to the students to do more activities, link the subjects to daily life and materialise them, use technology (video, flash, presentations, sides and so on) in their classes, solve more problems about the topic and the number of activities in workbook should be increased.
Keywords: Science Education; Force and Motion Unit; Problems and Suggestions for Solutions